Physiochemical characterization of a giant submandibular gland stone in a Nigerian patient - H.K. Omokanye; O.A. Wuraola; A.A. Baba; F.E. Ologe (Elsevier, 2021)
The incidence of sialolithiasis is about 12 cases per 1000 population and most cases occur in the submandibular gland, among adults in the 30-50 age groups. Since the early description of salivary calculus by Windsor in 1842, the etiology and exact mechanism of stone formation remain a subject of considerable research interest, while the chemical composition of analyzed stone often varies across studies globally. We analyzed the component elements and physiochemical morphology of a giant calculi extracted from the submandibular gland of an adult Nigerian. Our findings showed that the giant submandibular gland stone is rich in calcium (Ca), sodium (Na), potassium (K), iron (Fe), zinc (Zn), and manganese (Mn); while other elements occur in low or trace level.